2004
DOI: 10.1111/j.1582-4934.2004.tb00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in oxidative balance in rat pericytes exposed to diabetic conditions

Abstract: Recent data indicate that the oxidative stress plays an important role in the pathogenesis of diabetes and its complications such as retinopathy, nephropathy and accelerated atherosclerosis. In diabetic retinopathy, it was demonstrated a selective loss of pericytes accompanied by capillary basement membrane thickening, increased permeability and neovascularization. This study was designed to investigate the role of diabetic conditions such as high glucose, AGE‐Lysine, and angiotensin II in the modulation of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 49 publications
0
28
0
2
Order By: Relevance
“…One of the manifestations of metabolic syndromes such as obesity and diabetes is the production of excessive levels of ROS (26)(27)(28)(29)(30)(31) (21), culture of cells in medium containing high concentrations of D-glucose also activates ERK1/2, JNK, and p38, and inhibitors of these MAPK pathways inhibit high-glucose induction of KSHV gene expression. Interestingly, we found that high glucose levels and H 2 O 2 also cause the downregulation of the class III HDAC SIRT1, leading to increased levels of histone acetylation in the promoter region of the KSHV key lytic gene RTA.…”
Section: Discussionmentioning
confidence: 99%
“…One of the manifestations of metabolic syndromes such as obesity and diabetes is the production of excessive levels of ROS (26)(27)(28)(29)(30)(31) (21), culture of cells in medium containing high concentrations of D-glucose also activates ERK1/2, JNK, and p38, and inhibitors of these MAPK pathways inhibit high-glucose induction of KSHV gene expression. Interestingly, we found that high glucose levels and H 2 O 2 also cause the downregulation of the class III HDAC SIRT1, leading to increased levels of histone acetylation in the promoter region of the KSHV key lytic gene RTA.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few decades, the oxidative-stress-induced vascular dysfunction theory, which denotes a pathological condition characterized by the imbalance between ROS production and the ability of biological systems to detoxify the reactive intermediates, has become the focus of attention because of the pleiotropic effects of the oxidizing agents (Manea et al 2004;Simionescu 2007). Several mechanisms of oxidative stress have been proposed, including the overproduction of ROS, alterations in the antioxidant system, and the production of various oxygen intermediates (e.g., ONOO -, HO • ) that cannot be efficiently scavenged by the naturally occurring antioxidants (Lee et al 2009;Kondo et al 2009).…”
Section: Oxidative Stress In Vascular Inflammatory Disordersmentioning
confidence: 99%
“…Intracellular ROS generation was assessed using 6-carboxy-2 0 ,7 0 -dichlorodihydrofluorescein diacetate (H2-DCFDA) as described previously. 17 Cells were loaded with H2-DCFDA (2 mmol/l) for 30 min before the end of the incubation period (48 h). After washing twice with PBS, cells were scraped and disrupted by sonication on ice (20 s).…”
Section: Determination Of Intracellular Reactive Oxygen Species Genermentioning
confidence: 99%